2022
DOI: 10.3390/foods11233910
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality and Safety of Traditional Raw Milk Cheeses Manufactured on a Small Scale by Polish Dairy Farms

Abstract: Polish raw milk artisanal cheese may pose a threat to consumer safety due to pathogen presence. The aim of this study was to assess the microbiological safety, quality and physicochemical composition of cow’s and goat’s milk fresh cheeses produced by farmers on a small scale. A total of 62 samples of six cheese types were analyzed for Listeria monocytogenes, Salmonella spp., lactic acid bacteria and coliform presence and concentration levels. The physicochemical analysis estimated energy, water, protein, fat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…in artisanal raw milk cheeses [59]. Studies of traditionally produced cheeses in Brazil [85], Italy [23], Poland [86], Canada [87], and the United Kingdom [52] have also reported the absence of Salmonella spp. in traditionally made products, while 36% of samples from open markets and local stores in Hungary harboured high levels of Salmonella spp.…”
Section: The Presence Of Pathogens In Dairy Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…in artisanal raw milk cheeses [59]. Studies of traditionally produced cheeses in Brazil [85], Italy [23], Poland [86], Canada [87], and the United Kingdom [52] have also reported the absence of Salmonella spp. in traditionally made products, while 36% of samples from open markets and local stores in Hungary harboured high levels of Salmonella spp.…”
Section: The Presence Of Pathogens In Dairy Productsmentioning
confidence: 99%
“…In the current study, only one raw milk cheese (1.26%) was positive for L. monocytogenes, whereas 4.5% (n = 5) of kajmak samples harboured the pathogen (Table 3). While illnesses and listeriosis outbreaks have been linked to raw milk cheeses, in regions such as Brazil, Slovenia, Italy, and Poland [85,86,91,92], studies have also reported a general absence of L. monocytogenes in raw milk cheeses and only sporadic contamination was seen in the UK [52]. The primary route for pathogen introduction into dairies appears to be via contaminated raw milk [93].…”
Section: The Presence Of Pathogens In Dairy Productsmentioning
confidence: 99%
“…The first topic of the Special Issue, "Microbiological Safety and Quality of Fermented Products," includes two papers [1,2] that are both focused on the microbiological safety of fermented products. The first paper by Stefanou et al [1] investigated the microbiological safety, quality, and physicochemical composition of small-scale farmer's fresh cheeses made from cow's and goat's milk. The results showed that none of the samples contained Listeria monocytogenes or Salmonella spp.…”
mentioning
confidence: 99%